Inguinal hernia repair in preterm neonates: is there evidence that spinal or general anaesthesia is the better option regarding intraoperative and postoperative complications? A systematic review and meta-analysis. Issue 10 (8th October 2019) - Dohms, Katharina; Hein, Marc; Rossaint, Rolf; Coburn, Mark; Stoppe, Christian; Ehret, Constanze Barbara; Berger, Tanja; Schälte, Gereon
Abstract : Objectives: Whether spinal anaesthesia (SA) reduces intraoperative and postoperative complications compared with general anaesthesia (GA) was investigated. Design: The meta-analysis was structured based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. Databases (PubMed, MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Web of Science) were searched, and four randomised controlled trials (RCTs) and two retrospective cohort studies were included. A random-effects model with pooled risk ratios and mean differences with 95% CIs were used. Statistical heterogeneity was evaluated using the I 2 statistic. Quality assessment of the studies was performed by assessing the risk of bias according to the Cochrane and GRADE methodology. Setting: Publications from January 1990 to November 2018 were included. Participants and interventions: Our study selection captured information from studies focusing on neonates born before the 37th gestational week who were scheduled for an inguinal hernia repair operation under either SA or GA. Primary and secondary outcome measures: The primary outcome measures were apnoea, postoperative ventilation and method failure rates according to predefined eligibility criteria. The duration of surgery, desaturation events <80%, hospital stay duration and postoperative bradycardia were secondary outcomes. Results: We found significantly fewer events for the outcomes 'any episode of apnoea' and 'mechanical ventilation postoperatively' in the SA group. Bradycardias were significantly less common in the SA group. In total, 7.5% of the SA group were converted to GA. The duration of surgery was significantly shorter in the SA group. No significant differences were found in the outcome measures 'postoperative oxygen supplementation', 'prolonged apnoea', 'postoperative oxygen desaturation <80%' and 'hospital stay'. Conclusions: We consider SA a convenient alternative for hernia repair in preterm infants, providing more safety regarding postoperative apnoea. To the best of our knowledge, this is the first meta-analysis to include studies exclusively comparing SA versus GA. More high-quality RCTs are needed. Trial registration number: CRD42016048683